POTENTIAL VIOLATION OF RELIGIOUS NORMS IN STUDENT LIFE AT UNIVERSITY AND ITS ANTICIPATION - Marcia Monica; Agus Fakhruddin; Syivaul Hikmatul Hijiah (Fakultas Tarbiyah, Universitas Ibrahimy, 2024)
This research aims to explore the potential for violations of religious norms in the lives of students at the Indonesian University of Education and anticipatory strategies. The research background includes the important role of religious norms in shaping individual identity and behavior, especially in higher education environments which are often influenced by social pressure and academic demands. This research method involves surveys to identify factors that influence students in violating religious norms. The research results highlight various factors such as peer influence, high academic load, and lack of understanding of religious teachings. In conclusion, this research recommends anticipatory strategies involving educational approaches, social support, and fostering religious values ​​to prevent potential violations of religious norms among students.